60.3k views
2 votes
What is the equation of the axis of symmetry of the graph of y + 3x – 6 = –3(x – 2)2 + 4?

User Spg
by
5.6k points

2 Answers

6 votes

Answer:

the answer is A on edgen

Explanation:

User Frank Yin
by
6.2k points
4 votes

ANSWER


x =(3)/( 2)

EXPLANATION

The given equation is


y + 3x - 6 = - 3(x - 2)^(2) + 4

Expand the parenthesis:


y + 3x - 6 = - 3( {x}^(2) - 4x + 4) + 4


y + 3x - 6 = - 3 {x}^(2) + 12x + - 12 + 4

Write in standard form:


y = - 3 {x}^(2) + 12x - 3x+ - 12 + 4 + 6


y = - 3 {x}^(2) + 9x-2

where


a=-3,b=9,c=-2

The axis of symmetry is given by the formula:


x = - (b)/(2a)

Plug the values to get:


x = - (9)/( 2(- 3))


x =(3)/( 2)

The equation of axis of symmetry is


x =(3)/( 2)

User Debo
by
5.9k points